Amplifying youth voices: young people's recommendations for policy and practice to enhance vaccine acceptability - Oluwaseyi Dolapo Somefun; Marisa Casale; Genevieve Haupt Ronnie; Joshua Sumankuuro; Olagoke Akintola; Chris Desmond; Lucie Cluver (BMC, 2024)
Abstract Background The COVID-19 pandemic has underscored the need for increased vaccine availability and uptake, with vaccine hesitancy posing a significant barrier, particularly among young adults. Evidence from various countries highlight high levels of hesitancy among young people, necessitating targeted interventions. Engaging young adults as key stakeholders in shaping public health strategies is crucial, as their perspectives can enhance vaccine acceptance. This study aimed to assess the overall acceptability of the COVID-19 vaccine among young people and to explore the factors influencing their willingness or reluctance to be vaccinated now and in the future. Methods This study used qualitative data from 165 young adults in Nigeria, South Africa, and Zambia, to explore their suggestions for policies and strategies aimed at enhancing the acceptance of the Covid-19 vaccination among their age group. Data collection involved focus groups and interviews that explored participants' perceptions and recommendations regarding COVID-19 vaccination acceptability. Thematic analysis was used to analyse the data. Results Thematic analysis identified several factors influencing vaccine acceptability among young people and suggested recommendations to improve it. The themes included developing targeted communication strategies for accurate vaccine information, offering alternative vaccination methods, promoting vaccine education in schools, and using trusted public figures to share accurate information. Conclusions Persistent dissatisfaction with vaccine information dissemination underscores the need for more targeted communication strategies among young adults. Recommendations include developing non-injection vaccine options, incorporating vaccine education into school curricula and community programs, and leveraging influential public figures to build credibility. These insights are valuable for designing future programs to enhance vaccine acceptance among adolescents.